Solidarity for Myanmar: #MilkTeaAlliance Indonesia’s Transnational Activism in Pressuring the Government of Indonesia and ASEAN - Utama, Muhammad Anugrah (UI Scholars Hub, 2022)
The military coup in Myanmar on February 1, 2021, carried out by the Tatmadaw against top officials from the newly elected-government–in which National League for Democracy (NLD) Party made the majority–brought strong backlashes from civil society, one of which was the Milk Tea Alliance. This paper discusses the activism of Milk Tea Alliance Indonesia in pressuring the Indonesian government and ASEAN, especially during the ASEAN Special Summit. This paper is based on qualitative method using literature review on the case study of Milk Tea Alliance activism in Indonesia. By referring to the ‘Boomerang pattern’ framework on transnational advocacy network, this paper argues that the Milk Tea Alliance represents a valuable model in South-South civil society cooperation due to the multiplicity of channels, actor form, and issues. Therefore, it plays an essential role in decolonizing the unequal North-South relations in the initial concept of Keck & Sikkink. Furthermore, this article also exposes the role of regional norms in influencing the ‘boomerang pattern,’ making it difficult for the solidarity to push ASEAN & Indonesian government as the de-facto leader of ASEAN to act stricter on Tatmadaw.